Opec at (more than) fifty: the long road to baghdad, and beyond - Boue, J (Oxford Institute for Energy Studies, 2011)
Towards the beginning of the third volume of the History of the French Revolution, as overall proceedings are taking a sinister turn that will culminate in parliamentary regicide, Thomas Carlyle penned the following lamentation: ‘it is unfortunate, though very natural, that the history of this Period has so generally been written in hysterics. Exaggeration abounds, execration, wailing; and on the whole, darkness.’ These lines, aside from being a fine example of a pot calling kettles black, succinctly sum up both the tone and the explanatory sterility of much of the oceans of ink that have been spilled in the name of OPEC. However, the deep shadows in the field of OPEC historiography, more than a cause for regret, ought to be a source of shame for all concerned. After all, the fact that Carlyle himself could refer to History as the ‘distillation of rumour’, reflected in no small measure the difficulties still posed in his day by the collection, collation and dissemination of reliable information and data. Today, where contemporary issues are concerned, these difficulties have become sufficiently attenuated as to no longer constitute a credible excuse. Moreover, in the particular case of OPEC, it is clear that much of the prevailing darkness is the result of people ignoring (or even taking deliberate pot shots at) sound sources of illumination, with cover for this unedifying pursuit being provided by the din of axes being ceaselessly ground.